PERANCANGAN APLIKASI REKOMENDASI OBJEK PARIWISATA KOTA PEKANBARU BERBASIS ANDROID MENGGUNAKAN LOCATION BASED SERVICE UNTUK DINAS PARIWISATA KOTA PEKANBARU - Jan Alif Kreshna; Ibnu Surya; Kartina Diah Kusuma Wardani; Weslie Weslie (JURNAL ILMIAH INFORMATIKA, 2022)
Tourists who visit the city of Pekanbaru not only come from within the country, but also from abroad. To provide services to people inside and outside Pekanbaru City, the Pekanbaru City Tourism Office currently has an official website as a medium to convey information about tourist attractions in Pekanbaru City. On the website, there is already a list of tourist attractions in the city of Pekanbaru. This research will develop applications that can be used by tourists who will visit tourist attractions in Pekanbaru City. Applications developed based on Android will provide recommendations for tourist attractions that are around application users by utilizing the Location Based Service feature. The application will also be equipped with a map and use the BellmanFord algorithm to get the shortest route to that location. It is hoped that the application generated from this research can be used as an alternative media that can be used by the Pekanbaru City Tourism Office in order to provide the best service for people inside and outside Pekanbaru City.